Perception of Brazilian medical students toward organ donation - Batista,Eduardo Luis de Oliveira (2022)
SUMMARY OBJECTIVE: Brazil ranks second in gross numbers of kidney and liver transplantations, but deceased organ donation is still far below the national demand for organs. Apart from a high family refusal rate, another significant barrier is healthcare workers’ inappropriate knowledge concerning organ donation and transplantation. Since most of them have recently graduated from university, this study aimed to evaluate the awareness and attitudes of medical students concerning organ donation. METHODS: Between August and September 2021, a web-based survey with 10 overlapping questions was sent to medical students from several Brazilian universities after advertisements on social media. RESULTS: A total of 391 (60% female, mean age: 23 [17–41] years) students answered the survey. Most of them (91%) would like to donate organs in case of death, and 75% have already notified their family. The main reasons for not becoming a donor were fear of body manipulation (n=3) or family reaction (n=2) and religious reasons (n=2). When inquired, 54% were unaware of brain death criteria, and half of them claimed to have never discussed the topic in medical classes. Except for Glasgow coma scale (97%), pupillary (72%), and corneal (53%) reflexes, less than 25% knew other reflexes required for brain death diagnosis. CONCLUSION: Most medical students declared themselves as organ donors, and most informed their families. However, many students have never learned about crucial steps toward organ donation, which may impact their adequate recognition of potential organ donors later in life.